2018
DOI: 10.1186/s13002-018-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

Groundnut production constraints and farmers’ trait preferences: a pre-breeding study in Togo

Abstract: BackgroundGroundnut is an important legume crop in Togo. However, groundnut yield has been steadily decreasing for decades as a result of lack of organized breeding program to address production constraints. Though, low yielding varieties and late leaf spot have been often reported as the most important constraints, there is no documented evidence. Identifying and documenting the major production constraints is a prerequisite for establishing a good breeding program with clearly defined priority objectives and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The study revealed the existence of 8 different peanut folk varieties across the study area. This diversity is found to be very low compared to that found in Bolivia (62 distinct landraces) area of peanut origin [25] and higher than those encounter in Togo (4 varieties) [12] and Tanzania (8 varieties) [13]. The loss of peanut diversity in the study area is not alarming.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The study revealed the existence of 8 different peanut folk varieties across the study area. This diversity is found to be very low compared to that found in Bolivia (62 distinct landraces) area of peanut origin [25] and higher than those encounter in Togo (4 varieties) [12] and Tanzania (8 varieties) [13]. The loss of peanut diversity in the study area is not alarming.…”
Section: Discussionmentioning
confidence: 64%
“…In opposition to peanut farmers of Uganda [8], Tanzania [13], Ghana [26], Niger [27], Malawi [28], and Togo [12] for which insect pests and, diseases were the main constraints of t production, Beninese farmers perceived rodent attacks as the most constraint. This perception is share by Pakistan farmers, which also mentioned rodents as main constraint of peanut production [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abandonment of the groundnut sector for the bene t of other cash crops (cotton, sesame) by authorities (10) and the limited support from policies in groundnut breeding may be the causes of the disorganization of groundnut seed production system (46,47). In the Central-Western regions the high level of humidity thanks to a good annual rainfall exceeding 1000 mm (29), diseases were reported with predominant occurrence causing important loss of production (13,43,48). The high fertility of soil increased soil value which became out of reach for small farmer specially women.…”
Section: Discussionmentioning
confidence: 99%
“…PRA are nowadays acknowledged as a strong tool in plant breeding ensuring an e cient identi cation of farmer's constraints, preferences and also a large uptake of varieties and technologies. In Togo, (13) have conducted a PRA study as a pre-breeding activity to identify farmer's constraints and preferences in groundnut production. (14) used Participatory variety development as best approach to enhance sorghum germplasm and preserve local agrobiodiversity of this crop in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%